2011
DOI: 10.3389/fnhum.2011.00009
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Executive Functioning in Patients with Frontal Lobe Brain Damage with Goal Management Training

Abstract: Executive functioning deficits due to brain disease affecting frontal lobe functions cause significant real-life disability, yet solid evidence in support of executive functioning interventions is lacking. Goal Management Training (GMT), an executive functioning intervention that draws upon theories concerning goal processing and sustained attention, has received empirical support in studies of patients with traumatic brain injury, normal aging, and case studies. GMT promotes a mindful approach to complex real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
276
2
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 255 publications
(299 citation statements)
references
References 38 publications
15
276
2
6
Order By: Relevance
“…Other studies are single case-studies (Levine et al, 2000;Schweitzer et al, 2008;Metzler-Baddeley et al, 2010), or include small samples and are only partially randomized (Levine et al, 2011). Only two group-based GMT studies (Levine et al, 2011;Novakovic-Agopian et al, 2011) have reported follow-up analyses more than three months post-intervention, limiting the evidence for long-term effects.…”
Section: Tornås-goal Management Training In Abimentioning
confidence: 99%
See 4 more Smart Citations
“…Other studies are single case-studies (Levine et al, 2000;Schweitzer et al, 2008;Metzler-Baddeley et al, 2010), or include small samples and are only partially randomized (Levine et al, 2011). Only two group-based GMT studies (Levine et al, 2011;Novakovic-Agopian et al, 2011) have reported follow-up analyses more than three months post-intervention, limiting the evidence for long-term effects.…”
Section: Tornås-goal Management Training In Abimentioning
confidence: 99%
“…Reviews recommend metacognitive strategy training including self-monitoring and self-regulation as practice standard following ED due to traumatic brain injury (TBI) (Cicerone et al, 2011;Kennedy et al, 2008). Promising results have been reported for interventions such as problem solving therapy (Rath, Simon, Langenbahn & Sherr, 2003;Miotto, Evans, de Lucia & Scaff, 2008;von Cramon, Matthes-von Cramon & Mai, 1991) and goal management training (GMT; e.g., Levine et al, 2011), incorporating self-instructions aimed at strengthening the individual's ability to interrupt and control ongoing behavior.…”
Section: Tornås-goal Management Training In Abimentioning
confidence: 99%
See 3 more Smart Citations